Rethinking Quality Science Education for Climate Action: Transdisciplinary Education for Transformative Learning and Engagement - Kubisch, Susanne; Krimm, Hanna; Liebhaber, Nina; Oberauer, Karin; Deisenrieder, Veronika; Parth, Sandra; Frick, Melanie; Stötter, Johann; Keller, Lars (Frontiers in Education, 2022)
There is an urgent need for climate action on an individual and societal level, referring to the latest findings of the IPCC, as political regulations and technical advances won’t be enough to encounter climate change. Acknowledging young people’s role as present and future decision-makers, their engagement is imperative to achieve the Sustainable Development Goal 13 ‘Climate Action’. Therefore, new pathways of (teaching and) learning are necessary, encouraging transformative learning, which is assumed to lay the foundation for transformative engagement. Research in the field of science education attributes scientific literacy vision III to foster transformative learning and engagement. In this study, transdisciplinary education is analyzed as a promising concept that enables an exchange of knowledge, experience and perspectives between students and scientific partners, while jointly doing research on real-world issues. A quantitative analysis, capturing scientific literacy and transformative engagement for climate action of Austrian and German secondary school students (N = 162), as well as a literature review is carried out. This study reveals that the didactical concept of transdisciplinary education notably contributes to the implementation of scientific literacy vision III as well as II. According to the results, the three visions of scientific literacy are predictors for transformative engagement for climate action, assuming to be preceded by a transformative learning process. These encouraging findings need to be replicated by further scholars in other contexts.